2018
DOI: 10.1111/jocd.12685
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between: Carboxytherapy, platelet‐rich plasma, and tripolar radiofrequency, their efficacy and tolerability in striae distensae

Abstract: The three modalities of treatments proved to be effective clinically and histopathologically in treating both types of striae, which were well tolerated by the patients with minimal, transient side effects and our study results gave us guidelines for their clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 12 publications
4
57
2
1
Order By: Relevance
“…However, when these data are statistically analyzed, they show no difference compared to the control group. This study corroborates Ahmed and Mostafa study13 who also observed an increase in the amount of longer elastic fibers, observing as well that these fibers were thicker and evenly disposed after intradermal CO 2 injection. However, these authors did not perform morphometric analysis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, when these data are statistically analyzed, they show no difference compared to the control group. This study corroborates Ahmed and Mostafa study13 who also observed an increase in the amount of longer elastic fibers, observing as well that these fibers were thicker and evenly disposed after intradermal CO 2 injection. However, these authors did not perform morphometric analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Ahmed and Mostafa study 13 who also observed an increase in the amount of longer elastic fibers, observing as well that these fibers were thicker and evenly disposed after intradermal CO 2 injection.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations